PEMBERIAN ASI EKSKLUSIF DAN PENURUNAN BERAT BADAN IBU DI WILAYAH KERJA PUSKESMAS TENAYAN RAYA PEKANBARU - Desti Puswati (Marwah: Jurnal Perempuan, Agama dan Jender, 2012)
Breast feeding as a natural food is the best food that can be provided by a new mother to child birth. In addition to compositions suitable for infant growth and development which changes with baby's needs at any time. It also contains protective substances that can prevent infants from various infectious diseases. Breastfeeding also has a tremendous emotional effect which affects the inner relationship of mother and child and mental development of the child. This study aims to determine the relationship exclusive breast feeding with lower maternal weight in the working area of the health center Tenayan Raya, Pekanbaru.This type of research is quantitative research with correlation analysis research design. Accidental sampling technique is used. The collection of data using primary data and questionnaires measuring devices. Based on this research, the majority of respondents who gave exclusive breast milk that is 63 people (76%) and respondents who experienced weight loss of 59 people (71%), with x2 square test count (13) > x2 table (3.84). There is a relationship between exclusive breastfeeding with lower maternal weight.